Turkey’s Drought Status Associated with Climate Change - Emine Su Turan (Doğal Afetler ve Çevre Dergisi)
Due to various human activities, the accumulation of greenhouse gases in the atmosphere has increased rapidly since the industrial revolution. The most important consequence of the greenhouse effect, which is the result of greenhouse gas accumulation in the atmosphere, is that the earth's climate is warmer and more variable. On the other hand, climate change, whether global or regional, causes significant changes in the frequency, intensity, area distribution, length and timing of extreme weather and climate events. Potential impacts of global climate change; known to have some impacts already both globally and locally, intensify on clean water resources, agriculture, forests, sea level, energy, human health and biodiversity. It is estimated that our country is among the countries of risk group in terms of the possible effects of the global climate change and will be affected more by the climate change in the future especially in the Mediterranean and Central Anatolia regions. One of the most harmful and least recognized natural disasters is drought. There are many reasons for the increase in drought in our semi-arid climate. It is at the top of these that climate change and precipitation are very different from places where water is needed. Climate change projections show that temperatures will rise throughout the country and precipitation will decrease especially in the southern half of the country. It is inevitable that these changes will affect the water resources of our country in the negative direction and decrease the water potential especially in the southern basins.